Principios teórico-prácticos de la pedagogía activa y el impacto que producen en el desarrollo sensorio motriz de los niños/as del cibv, “Jerónimo Orión LLaguno”, cantón Pueblo Viejo, provincia de los Ríos - Morante Pino, Vanessa Lorena (2016)
Its theoretical foundation which supports the model for the development of thinking and its applications rests on theories about the functioning of the mind stimulation of intellect and cognitive phenomena accompanying the mental act. This investigative work of broken down into the following chapters: In the first chapter, we'll talk about the problem macro, micro, meso, of the analyze critic, prognosis, justification, General and specific objectives In the first chapter, we'll talk about the problem macro, micro, meso, of the analyze critic, prognosis, justification, General and specific objectives Chapter II have the theoretical framework, background variables operacionalita Research Foundation In chapter III, we have the methodology, here sets qualitative and quantitative, approach mode, using the techniques bibliographical and research field, the type of research based on a correlation of Variables, sample research of 28 students and 8 teachers and 1 rector determines the operationalization of the independent Variable and dependent, as well as the plan for the collection and processing of information. Chapter IV presents the analysis and interpretation of the results obtained in the applied survey. Chapter V consists of conclusions and recommendations. Chapter VI contains the proposal posed to the established problems. In the annexes, attached the surveys and data that have been collected for the development of research, taking as a reference the personal analysis.